Temporal association of diffuse large B-cell lymphoma with PD-1 inhibitor therapy in a patient with gastric adenocarcinoma: a case report - Jiang, Yiqing; Wu, Kun; Hu, Jia; Yu, Mingxin; Xu, Yuhang; Xu, Zihan; Cao, Rongxuan; Zhang, Yi; Gao, Yanfang; Liu, Shuzhen; Ding, Yanhong (Frontiers in Immunology, 2026)
BackgroundImmune checkpoint inhibitors (ICIs) have demonstrated substantial clinical benefit across a wide range of malignancies. With their expanding use, uncommon immune-related events, including hematologic abnormalities and lymphoid proliferations, are increasingly recognized. However, a causal relationship between ICI exposure and lymphoma development remains unproven.Case descriptionWe report a 70-year-old woman with moderately to poorly differentiated gastric adenocarcinoma who was diagnosed with diffuse large B-cell lymphoma (DLBCL) during postoperative treatment with FOLFOX chemotherapy combined with the PD-1 inhibitor sintilimab. During therapy, the patient developed recurrent pleural and pericardial effusions. Early pleural fluid cytology revealed atypical lymphoid cells with occasional Epstein–Barr virus–encoded RNA (EBER) positivity, but immunophenotypic and clonality assessments were not performed, precluding a definitive lymphoma diagnosis at that time. Subsequent cytological, immunophenotypic, and molecular studies confirmed Ann Arbor stage IV DLBCL, predominantly presenting as malignant effusions. The patient achieved remission with R-CHOP therapy but later experienced relapsed and refractory disease.ConclusionThis case illustrates a temporal association between PD-1 inhibitor–based therapy and the diagnosis of DLBCL. Given the lack of baseline systemic staging, overlapping PET/CT findings, early diagnostic uncertainty in effusion cytology, and potential contributions from chemotherapy-induced immune perturbation and EBV-associated processes, a direct causal relationship cannot be established. This report underscores the importance of comprehensive baseline evaluation and cautious interpretation of atypical lymphoid findings during immunotherapy.